Replacing Members with Managers? Mutualism among Membership and Nonmembership Advocacy Organizations in the United States - Walker, Edward T.; McCarthy, John D.; Baumgartner, Frank (The American journal of sociology, 2011)
Associations with a professional staff but no members (nonmembership advocacy organizations, or NMAOs) are the subject of lively debate. Many argue that their proliferation has allowed an expansion of advocacy without an accompanying growth in civic engagement. This article asks if there has been significant recent growth of NMAOs and if those organizations have displaced membership advocacy organizations (MAOs). The authors find no evidence for a proportional increase of NMAOs since the 1960s. Further, among all organizations in three populations -- peace, women's issues, and human rights -- NMAOs have not displaced MAOs. In particular, the authors find that MAO density shapes NMAO founding, as membership groups provide a base for professional advocacy. These findings challenge the notion that U.S. civic life has undergone a systemic transformation away from organizational forms that promote civic engagement. Adapted from the source document.